Development and Validation of a State-Based Measure of Emotion Dysregulation: The State Difficulties in Emotion Regulation Scale (S-DERS). (March 2017) - Lavender, Jason M.; Tull, Matthew T.; DiLillo, David; Messman-Moore, Terri; Gratz, Kim L.
Existing measures of emotion dysregulation typically assess dispositional tendencies and are therefore not well suited for study designs that require repeated assessments over brief intervals. The aim of this study was to develop and validate a state-based multidimensional measure of emotion dysregulation. Psychometric properties of the State Difficulties in Emotion Regulation Scale (S-DERS) were examined in a large representative community sample of young adult women drawn from four sites ( N = 484). Exploratory factor analysis suggested a four-factor solution, with results supporting the internal consistency, construct validity, and predictive validity of the total scale and the four subscales: Nonacceptance (i.e., nonacceptance of current emotions), Modulate (i.e., difficulties modulating emotional and behavioral responses in the moment), Awareness (i.e., limited awareness of current emotions), and Clarity (i.e., limited clarity about current emotions). S-DERS scores were significantly associated with trait-based measures of emotion dysregulation, affect intensity/reactivity, experiential avoidance, and mindfulness, as well as measures of substance use problems. Moreover, significant associations were found between the S-DERS and state-based laboratory measures of emotional reactivity, even when controlling for the corresponding original DERS scales. Results provide preliminary support for the reliability and validity of the S-DERS as a state-based measure of emotion regulation difficulties.